2021
DOI: 10.1111/ans.17209
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for recurrence in colorectal cancer: a retrospective analysis in a regional Australian hospital

Abstract: Background Colorectal cancer is the third most commonly diagnosed malignancy in Australia. Up to a third of patients who have undergone surgery with curative intent for colorectal cancer will have a recurrence of disease leading to significant morbidity and mortality. Regional Australians have disproportionately worse outcomes. Aim To identify factors associated with recurrence in colorectal cancer patients treated at a regional Australian hospital. Methods This study is a retrospective cohort analysis. Consec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 11 publications
0
9
1
1
Order By: Relevance
“…Among the 498 postoperative CRC included in this study, 51 patients (10.24%) experienced early recurrence and metastasis, which is slightly lower than the result (13.91%) reported by Australian scholars 31 . It could be explained by the fact that the participants in the Australian study were patients with CRC from remote locations.…”
Section: Discussioncontrasting
confidence: 61%
“…Among the 498 postoperative CRC included in this study, 51 patients (10.24%) experienced early recurrence and metastasis, which is slightly lower than the result (13.91%) reported by Australian scholars 31 . It could be explained by the fact that the participants in the Australian study were patients with CRC from remote locations.…”
Section: Discussioncontrasting
confidence: 61%
“…Also, results showed that pT4 (HR: 4.06, 95%CI: 1.60-10.29, p = 0.003) was a risk factor for mortality [ 9 ]. Another study was conducted to recognize factors affecting recurrence in patients with colorectal cancer at a regional Australian hospital [ 10 ]. The study by Heinemann and Karl aimed to provide a brief overview of clinics, diagnosis, and management of some of the best colorectal cancer predispositions in this regard [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…По данным литературы, на частоту рецидивов влияют гистотип опухоли, уровень Cа19-9, периневральная и лимфоваскулярная инвазия, метастатическое поражение лимфатических узлов, менее 12 исследованных лимфоузлов, Т4 стадия опухоли и экстренный характер операции [11,12]. Нами не выявлена зависимость развития рецидива опухоли и каких-либо прогностических факторов, что, видимо, также обусловлено малым количеством рецидивов в нашем исследовании.…”
Section: Discussionunclassified